2009
DOI: 10.1088/1367-2630/11/3/033003
|View full text |Cite
|
Sign up to set email alerts
|

Environment-assisted quantum transport

Abstract: Abstract. Transport phenomena at the nanoscale are of interest due to the presence of both quantum and classical behavior. In this work, we demonstrate that quantum transport efficiency can be enhanced by a dynamical interplay of the system Hamiltonian with pure dephasing induced by a fluctuating environment. This is in contrast to fully coherent hopping that leads to localization in disordered systems, and to highly incoherent transfer that is eventually suppressed by the quantum Zeno effect. We study these p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

58
1,169
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 831 publications
(1,229 citation statements)
references
References 40 publications
58
1,169
2
Order By: Relevance
“…This finding mirrors the results found in the transport analysis of the FMO complex 9,16 and demonstrates that no fine-tuning of specific vibrational modes is required to sustain robust and efficient environmentally assisted energy transfer. 11,12,56 5 Chlb/Chla transfer time-scale in LHC II LHC II has been extensively studied within the Redfield, Förster, and interpolating approximations. Without an exact solution of the open system dynamics obtained with QMaster, the error made by the approximate methods is undefined and it is not known which approximation works best for a specific system.…”
Section: Influence Of the Vibrational Peaks On The Transport In Lhc IImentioning
confidence: 99%
See 1 more Smart Citation
“…This finding mirrors the results found in the transport analysis of the FMO complex 9,16 and demonstrates that no fine-tuning of specific vibrational modes is required to sustain robust and efficient environmentally assisted energy transfer. 11,12,56 5 Chlb/Chla transfer time-scale in LHC II LHC II has been extensively studied within the Redfield, Förster, and interpolating approximations. Without an exact solution of the open system dynamics obtained with QMaster, the error made by the approximate methods is undefined and it is not known which approximation works best for a specific system.…”
Section: Influence Of the Vibrational Peaks On The Transport In Lhc IImentioning
confidence: 99%
“…4 On top of the relaxation process, oscillatory components prevail in 2d-spectra which contain signatures of electronic coherences and specific vibrational modes. 6,[8][9][10] The coupling to the environment determines the transfer efficiency in LHCs 11,12 through the bath-correlation time of the phonon bath, [13][14][15] the shape of the continuum part of the spectral density, 9,16 and specific structures within the spectral density. 9,17 For the FMO complex, the superohmic character of the spectral density results in long-lasting electronic coherences despite a strong coupling to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical understanding of the experiments is in its early stages and atomistic simulations based on molecular dynamics have not reached agreement [12,13]. A calculation of 2d echo-spectra based on the molecular dynamics simulation [14] does not show clear coherent oscillations at T = 277 K. One key ingredient for efficient transfer dynamics is the strong coupling to vibronic modes, which induces energy dissipation [10,11,15]. For the FMO complex the thermalization occurs within picoseconds and was observed by Brixner et al by the decay of diagonal-peak amplitudes to lower energies [16].…”
mentioning
confidence: 99%
“…In 2d spectra long-lasting beatings are observed, ranging from 1.2 ps at T = 150 K to 0.3 ps at T = 277 K [9]. The interplay of coherent dynamics, which leads to a delocalization of an initial excitation arriving at the FMO network from the antenna, and the coupling to a vibronic environment with slow and fast fluctuations, has lead to studies of environmentally assisted transport in LHCs [10,11].An important open question is whether coherence plays a key-role in the functioning of light-harvesting complexes [8]. The theoretical understanding of the experiments is in its early stages and atomistic simulations based on molecular dynamics have not reached agreement [12,13].…”
mentioning
confidence: 99%
“…At the same time first experimental studies have shown that quantum coherence can play a significant role in photosynthetic light-harvesting complexes [10][11][12] and in chromophoric energy transport [13]. Since one of the main results found in many of these studies is the existence of enhanced transport efficiency in the presence of noise [6,7,10,14,15], it has become clear that understanding the dynamics of noisy quantum state transport can play a significant role in modeling and understanding natural physical and bio-chemical processes. Identifying models and dynamics in which the effect of the noise contributes constructively to the transport efficiency is therefore an important task.…”
Section: Introductionmentioning
confidence: 99%